2022
DOI: 10.1109/tits.2022.3146793
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Measures of Risk Perception in Highly Automated Driving

Abstract: Highly automated driving will likely result in drivers being out-of-the-loop during specific scenarios and engaging in a wide range of non-driving related tasks. Manifesting in lower levels of risk perception to emerging events, and thus affect drivers' availability to take-over manual control in safety-critical scenarios. In this empirical research, we measured drivers' (N = 20) risk perception with cardiac and skin conductance indicators through a series of high-fidelity, simulated highly automated driving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In recent years, AV safety has become a key indicator of concern influencing user intention to adopt AVs following reports of traffic accidents involving AVs. Previous studies have shown that the safety risks of AVs and their scope are increasingly valued by users (Karnouskos 2021;Perello-March et al 2022).…”
Section: Safety Risk Perception Associated With Avsmentioning
confidence: 99%
“…In recent years, AV safety has become a key indicator of concern influencing user intention to adopt AVs following reports of traffic accidents involving AVs. Previous studies have shown that the safety risks of AVs and their scope are increasingly valued by users (Karnouskos 2021;Perello-March et al 2022).…”
Section: Safety Risk Perception Associated With Avsmentioning
confidence: 99%
“…Some of them might have kept in mind they were in a driving simulator, while some others had mentioned they thought it was a spam and did not pay much attention to it. Recent work suggesting that drivers' perception of risk in automated driving was diminished in simulators supports that assumption (Perelló-March et al, 2022). Despite the limitations of it being a simulator research, the results still showed that the experiment was engaging enough to draw their attention and not ignore the HMI.…”
Section: Limitations Implications and Future Researchmentioning
confidence: 79%
“…Also, reaction times were found to be higher in automated driving compared to manual driving, which they attribute to potential mental underload (Young and Stanton 2007). On the other hand, Perello-March et al (2022) state that some NDRTs performed during highly automated driving may also increase arousal above the optimum and therefore decrease performance.…”
Section: Understand the Context Of Use And Identify User Requirements...mentioning
confidence: 96%